Strategi Peningkatan Pertumbuhan dan Produktivitas Bawang Merah (Allium ascalonicum L.) melalui Kombinasi Mulsa dan Pupuk Kandang Ayam - Reza, Reza; Kahar, Kahar; Sondakh, Rian Christian (Permaculture: Jurnal Ilmu Pertanian & Lingkungan, 2025)
Shallots (Allium ascalonicum L.) are one of the important horticultural commodities in Indonesia whose productivity is greatly influenced by cultivation techniques, especially mulch and organic fertilizer. This study was conducted to increase the growth and yield of shallots through various types of mulch and doses of chicken manure. The study was conducted in the Faculty of Agriculture practice field, Madako University, Tolitoli, Tolitoli Regency, Central Sulawesi, for three months, from February to April 2024. The design used was a two-factor Randomized Block Design (RBD), namely the type of mulch (M0: without mulch, M1: rice husk charcoal, M2: plastic mulch) and the dose of chicken manure (K0: without fertilizer, K1: 10 tons/ha, K2: 20 tons/ha), each with three replications. Data were analyzed using analysis of variance (ANOVA), followed by the Least Significant Difference (LSD) test at the 5% level. The results showed that the plastic mulch treatment (M2) significantly affected the fresh weight of tubers with leaves, the fresh weight of tubers without leaves, and the number of tubers. Meanwhile, a dose of 20 tons/ha of chicken manure (K2) significantly affected the fresh weight of tubers both with and without leaves. The interaction between the two factors was insignificant, so their effects were independent. Thus, increasing the dose of chicken manure (K2) still produced the highest yield regardless of the type of mulch used.